Sourdoughs of Spontaneous (Natural) Fermentation in Modern Bakery Production - Irina M. Zharkova; Yuriy F. Roslyakov; Danil S. Ivanchikov (Техника и технология пищевых производств)
Sourdough bakery products have a wide range of tastes and aromas, an extended shelf-life, and other benefits that are important for food producers and consumers. Recent years have seen a growing research interest in the microbiome of bakery sourdoughs. The research objective was to generalize, systematize, and analyze modern data on spontaneous fermentation starters, their production methods, and their role in the technological process at modern bakeries. The study featured domestic and foreign monographs, research articles, and patents related to various aspects of the production and commercial use of spontaneously fermented baking starters. The search covered publications indexed in PubMed and eLIBRARY.RU in 2000–2022. The sources were selected based on such indicators as completeness, consistency, reliability, and relevance. The obtained data were analyzed and systematized in line with the method of apperception and holography. The analysis focused on the factors that affect the microbiome of baking starter cultures, in particular, spontaneous fermentation. Another aspect included the effect of the raw materials used at the stage of breeding spontaneous fermentation starter cultures on their quality indicators. The transformation of bioactive compounds in the process of sourdough fermentation proved to be an increasingly relevant research matter. Food producers are looking for more effective tools to develop bakery products with specific nutritional properties, e.g., lower glycemic index, increased content of bioactive nutrients, reduced acrylamide content, low gliadin allergenicity, etc. The isolation and profiling of microorganisms included in the microbiome of spontaneous fermentation sourdough cultures is of practical interest because new strains might produce starter cultures intended for various target audiences.